Borrowings of law as a means of improving the national legal system - A. V. Skorobogatov (Russian Journal of Economics and Law)
Objective: to comprehensively study the borrowings of law as a means of improving the national legal system. Great attention is paid to the classification of legal borrowings and the specifics of these processes in modern Russia.Methods: the methodological basis of the research is the synthesis of classical and post-classical ideological paradigms, which determined the choice of specific research methods: formal-legal, comparative, method of legal modeling, hermeneutic, discursive.Results: the article studies the legal category of “borrowings of law”. Based on the study of content, focus and methods of law borrowings, their classification (reception of law, legal dialogue, legal acculturation, legal transfer, legal expansion) is proposed. The author’s interpretation of these concepts and their role in improving the national legal system is given. Special attention is paid to the nature and significance of law borrowings in Russia. The conclusion is made that the effective legal system development is possible only under the combination of legal borrowings and national legal values. Scientific novelty: for the first time, the article analyzes the essence and content of law borrowings from post-classical viewpoint, their classification is given, defines their role in the legal development of modern Russia.Practical significance: the main provisions and conclusions of the article can be used in scientific and educational activities when considering the essence and content of legal development.